Comparison of the content of active compounds in cell suspensions and aqueous extracts of Rosmarinus officinalis L. with those in the Endophytic fungus Alternaria alternata - Abed, Rabab; Mohammed Alwan, Batoul (Iraqi Journal for Applied Science, 2024)
The current study was carried out to detect the active compounds in both the aqueous extract of a Rosmarinus officinalis L. plant and the extract of cell suspensions and compare them with the extract of the endophytic fungus Alternaria alternata isolated from the leaves of an R. officinalis plant. Callus was induced from the leaves of rosemary plants, and the highest induction of callus formed reached 100% when treated with a concentration of 1-Naphthaleneacetic Acid (NAA) 2.0 mg. L-1, compared to the control treatment, which had an induction rate of 0%. The highest fresh weight of the callus was 1.628 gm in the presence of NAA. The callus induced in the presence of NAA was characterized by its fragile texture. Cell suspensions were also obtained from it. The fungus extract was superior in its content of active compounds to the aqueous extract and cell suspension cultures at 21 days. The total alkaloid content was 6.65%, phenolic content was 117.25 mg. gm, flavonoid content was 104.35 mg. gm, total terpenoid content was 6.65%, total steroid content was 6.05%, and the concentration of rosemary acid was 154.7%. The results of the current study confirm the single receptor of endophytic fungi isolated from medicinal plants as one of the important sources of effective compounds.